Pengaruh Treatment Double Action: Dark Chocolate dan Teh Chamomile terhadap Nyeri Dismenore pada Mahasiswi Kebidanan Universitas X Gombong, Kebumen - Rahmadhani, Wulan; Mutoharoh, Siti; Dewi, Adinda Putri Sari (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Menstruation is a sign of female puberty. During menstruation, women will experience complaints such as menstrual pain or cramps known as dysmenorrhea. Dysmenorrhea is the most common gynecological problem. This study aims to identify the effect of double action treatment using dark chocolate and chamomile tea on dysmenorrhea pain. This quantitative study used a pre-experimental method with a one-group pretest post-test design. The population in this study was 114 female students with a sample size of 53 respondents selected using the Slovin formula. The results of the study showed a change in the mean value of 3.057 with 95% CI: 2.957-3.156 indicating the influence of providing dark chocolate on the dysmenorrhea pain scale. The mean value change in the group receiving dark chocolate reached 3.057. Besides, there was a change in the mean value of 2.057 with 95% CI: 1.973-2.141 indicating the influence of providing chamomile tea on the dysmenorrhea pain scale. Dark chocolate and chamomile tea are simple non-pharmacological treatments to reduce the scale of pain which are quick to process because they can improve the mood of the users to reduce their scale of pain. Thus, an improved mood with an increased feeling of relaxation after taking one of these items will stimulate the glands in the brain to reduce the pain scale of dysmenorrhea.